An Attitudinal Appraisal Analysis of Beauty Product Review on James Charles YouTube Videos - Wulandari, Agesta Putri; Khristianto, Khristianto (ITScience (Information Technology and Science), 2024)
This research aims to explain and evaluate how James Charles uses appraisal in YouTube videos. The research focuses on analyzing the types of attitudinal appraisal used in the videos. Appraisal is a connection meaning how language use deals with relationships and communicates related to feelings. The study used descriptive qualitative research that attempts to provide an in- depth analysis and explanation about the subject. The sentences collected from James Charles YouTube videos were used as the research data. Beauty vloggers is a person who made and share makeup content related to the videos on social media platforms such as YouTube This research used 2 videos from YouTube account James Charles. First video with title TRYING A FULL FACE OF MAKEUP FROM FOREVER 21 and second video with title TRYING A FULL FACE MAKEUP FROM ALIEXPRESS. To obtain the data, the researcher first watched the videos, then transcribed it and watched it again to ensure the transcript was accurate. The researcher used Martin and White theory called appraisal, specifically their classification of attitudes appreciation, judgement, and affection to examine the data. The research reveals that there are 21 appreciations, 28 affect, and 19 judgement from the video which applied attitudinal appraisal in James Charles YouTube video. From the total, the most dominant type is affect, the second one is appreciation, and the last used is judgement.